2014
DOI: 10.1002/2013gl058918
|View full text |Cite
|
Sign up to set email alerts
|

A ubiquitous low‐velocity layer at the base of the mantle transition zone

Abstract: Global stacks of receiver functions clearly exhibit the upper mantle stratification. Besides the most prominent seismic discontinuities, such as the Moho and the 410 and 660 km discontinuities, a negative discontinuity is detected at a depth of~600 km, indicating a low-velocity layer at the base of the mantle transition zone. The slant-slack technique helps to identify the primary conversions from the multiple reverberations. Presence of the negative 600 km discontinuity underneath both continent and ocean isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 34 publications
2
48
0
Order By: Relevance
“…Up to our knowledge, there exists no known mineralogical phase change that would produce the negative signal before P660s. Other studies have also observed similar negative impedance features and have interpreted them as accumulated oceanic crust at the base of the TZ (Eagar et al, 2010;Shen and Blum, 2003;Shen et al, 2008Shen et al, , 2014. This signal is not used in the following analysis, and therefore, we do not further explore its origin.…”
Section: Negative Amplitude Precursory Signalsmentioning
confidence: 83%
“…Up to our knowledge, there exists no known mineralogical phase change that would produce the negative signal before P660s. Other studies have also observed similar negative impedance features and have interpreted them as accumulated oceanic crust at the base of the TZ (Eagar et al, 2010;Shen and Blum, 2003;Shen et al, 2008Shen et al, , 2014. This signal is not used in the following analysis, and therefore, we do not further explore its origin.…”
Section: Negative Amplitude Precursory Signalsmentioning
confidence: 83%
“…It is also associated with a velocity reduction (−20% of the reflection amplitude at the '410'). Its origin remains mysterious although Shen et al (2014) suggest that this discontinuity is a global feature associated with delamination and accumulation of oceanic crust at the top of the lower mantle.…”
Section: Resultsmentioning
confidence: 99%
“…The mantle transition zone (MTZ) is an ∼250‐km‐thick boundary layer delimited by two seismic interfaces, the so‐called 410‐ and 660‐km discontinuities, which are attributed to solid‐solid phase changes from olivine (ol) to wadsleyite (wa) and ringwodite (rw) to perovskite+magnesiowustite (ppv+mw; Bina & Helffrich, ). An enigmatic patchwork of low‐seismic velocity zones (LVZs) was reported at various scales and depths within or surrounding the MTZ (e.g., Shen et al, ; Tauzin et al, , Tauzin, Kim, & Kennett, ; Vinnik & Farra, ). These LVZs might be distinctive features of a well‐mixed convective mantle that preserves small‐scale compositional heterogeneities.…”
Section: Introductionmentioning
confidence: 99%
“…These LVZs might be distinctive features of a well‐mixed convective mantle that preserves small‐scale compositional heterogeneities. They are usually attributed to the volatile content (H 2 O, CO 2 ; Bercovici & Karato, ; Hier‐Majumder & Tauzin, ) or to remnants of subducted oceanic crust in the MTZ (Shen & Blum, ; Shen et al, ). High‐resolution mapping of these LVZs at regional scale is thus crucial for our understanding of the recycling of geochemical heterogeneities within large‐scale limbs of thermally driven mantle convection (Tauzin, Kim, & Kennett et al, ; Wei & Shearer, ).…”
Section: Introductionmentioning
confidence: 99%